THE CORRELATION AMONG READING ATTITUDE, THE USE OF INTERNET AND READING COMPREHENSION - Rahmawati Umbara; Machdalena Vianty; Rita Inderawati (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2015)
Abstract: The aim of this study was to investigate the correlation among reading attitude, the use of internet and reading comprehension of English Study Program Students of PGRI University. Questionnaires and a test were administered to the sample (N=152). Pearson product-moment correlation was used to analyse the data. The result showed a significant correlation between the students‟reading attitude and their reading comprehension (r=.562), the students‟ use of internet and reading comprehension (r =.200). The findings also revealed the correlation between the aspects of reading attitude and reading comprehension: prevailing feelings about reading (r=.553), action readiness for reading (r =.536) and evaluative beliefs about reading (r = .442). Furthermore, to reading comprehension, regression analysis discovered that reading attitude contributed 31.5%, two aspects of reading attitude (prevailling feelings about reading and action readiness for reading) contributed 33.7% and the use of internet contributed 4%.Key words: reading attitude, the use of internet, reading comprehension